Von Grafen und Predigern: zur Reformationsgeschichte des Mansfelder Landes , [... Tagungen, die in den Jahren 2010 und 2011 in Eisleben und Mansfeld] - Kohnle, Armin; Bräuer, Siegfried (Schriften der Stiftung Luthergedenkstätten in Sachsen-Anhalt, 2014)
This volume collects the contributions of two conferences in 2010/2011 in Eisleben and Mansfeld. The focus of the first conference was on Count Albrecht von Mansfeld and his court chaplain Michael Coelius. Another Protestant preacher, Kaspar Güttel, was the central character of the second conference. This triad, Albrecht - Coelius - Güttel, had a substantial impact on the history of the County of Mansfeld. The articles on these three historical figures are at the center of this volume. Together with futher biographical and thematic studies they provide a much more defined picture of the Reformation history of Mansfeld Land